Human body - Rogers, Kirsteen; Henderson, Corinne (Tulsa, OK : EDC, 2002)
Discusses how we breathe, why we eat, what blood is made of and much more about the human body.
Human body -- Cells -- Skeleton -- Muscles -- Circulatory system -- Teeth -- Digestion -- Food and diet -- Respiratory system -- Energy for life -- Balancing act -- Nervous system -- Brain -- Skin, nails and hair -- Eyes -- Ears -- Nose and tongue -- Reproduction -- Growing and changing -- Genetics -- Gene technology -- Fighting disease -- Medicine -- Facts and lists -- A-Z of scientific terms -- Test yourself -- Index -- Acknowledgments.
Includes index.
9 - 12 years
Keywords: Human body; Human Body -- Computer network resources; Cells; Circulatory system; Respiratory system; Nervous system; Reproduction